PERSEPSI GEN X DAN MILENIAL TERHADAP KONTEN EDUKASI SEKSUAL DI AKUN INSTAGRAM @taulebih.id - Septiani, Tiara (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
The focus of this article is on the perception of Gen X and Millennials towards sexual education content that is climbed in open spaces such as the social media account Instagram @taulebih.id. Discussions on sexual education issues are still a taboo and sensitive topic that is often associated with negative connotations. However, from the results of this research through online interviews with 7 informants, they agreed and agreed with the sexual education content disseminated through social media. The analysis of informant perception is categorized based on Stuart Hall's theory of audience acceptance in three positions: dominant-hegemonic reading, negotiated reading, and oppositional reading based on how the audience responds to and interprets the text. 4 out of 7 informants occupied the dominant-hegemonic reading position, 2 of them occupied the negotiated reading position, and 1 person in the oppositional reading position. 4 informants who occupy the dominant position agree meaningfully that the message is in line with the message conveyed by the sender, 2 informants in the negotiation position argue that they are in line with the message conveyed by the sender only that it is negotiated on their personal beliefs, while 1 informant in the position of the opposition is very opposed and not in line with the message sent by the sender or the content of the message.